Stress Test of BPRS and BUS Capital for the 2014-2022 Period Using the ECL Approach - Nisa', Isma Mufidatun; Oktaviana, Ulfi Kartika (Universitas Negeri Padang, 2024)
The operation of BUS and BPRS cannot be separated from the risks experienced, one of which is capital risk. The capital stress test used to calculate the capital adequacy of BUS and BPRS is the calculation of Expected Credit Loss (expected loan loss). ECL is the result of multiplying PD, LGD, and EAD. This study aims to determine the assessment and differences in capital stress tests using the ECL approach in BUS and BPRS. This research uses a descriptive quantitative approach. The method used is purposive sampling. The samples of this study were 12 BUS and 3 BPRS. The data used is secondary data in the form of annual financial reports taken from the official websites of BUS and BPRS for 2014-2022. The results of this study indicate that the assessment of the capital stress test using the ECL approach on BUS is classified as stage 1 (performing), and BPRS is classified as stage 2 (under-performing). A significant difference was found between BUS and BPRS.